China’s South-to-North Water Diversion Project : A Review and Reach Beyond China’s Borders - Jia, Yi; Zhang, Linus ; 0000-0003-2676-3420; Niu, Jianzhi; Berndtsson, Ronny ; 0000-0003-1473-0138 (Water, 2025)
The South-to-North Water Diversion Project (SNWDP), the world’s largest water transfer initiative, is designed to address northern China’s acute water scarcity by diverting approximately 45 km3 of water annually from the south through three major routes, with completion targeted for 2050. This review demonstrates that the SNWDP has already improved water security for over 150 million people, stabilized groundwater, and supported agricultural and urban development, but also presents significant challenges, including escalating costs, large-scale resettlement, and substantial environmental concerns such as ecosystem alteration, salinity intrusion, pollutant transfer, and risks to biodiversity and water quality. While mitigation and adaptive management efforts are ongoing, their long-term effectiveness remains uncertain. Notably, the SNWDP’s influence extends beyond China: by enhancing food production self-sufficiency, it can help stabilize global food markets during concurrent droughts and serves as a model—albeit a debated one—for large-scale water management and governance. The project’s hydropolitical and geopolitical dimensions, especially regarding the planned western route and potential transboundary impacts, underscore the need for international dialog and monitoring. Overall, the SNWDP exemplifies both the opportunities and dilemmas of 21st-century megaprojects, with its legacy dependent on balancing economic, environmental, and social trade-offs and on transparent, participatory governance to ensure sustainable outcomes for China and the global community.